Pengolahan Limbah Penggilingan Padi Menjadi Bioplastik menggunakan palstisizer Sorbitol - Kartika Udyani; Krisnadi Rinto; Yuni Handarni (Journal of Industrial Process and Chemical Engineering (JOICHE), 2021)
Research on the manufacture of bioplastics from bran is one of the efforts todevelop the development of environmentally friendly plastics because they can bedecomposed by microorganisms. In addition, this study also seeks to reduceenvironmental pollution due to the disposal of rice mill waste. The research wasconducted by mixing rice bran with water, sulfuric acid and sorbitol in variousvariations of the ratio of sorbitol and bran 1:10; 2:10; 3:10; 4:10 and 5:10 (v:b).Furthermore, chitosan was added as a reinforcement with variations in theaddition of chitosan with bran, namely 4:10; 6:10; 8:10; 10:10 and 12:10 thenprinted and analyzed for dance strength, swelling and surface morphology. Thetest results showed the highest tensile strength value in the ratio of sorbitol andbran 5:10 and chitosan bran 10:10 with the highest tensile strength value of 64.27MPa and 25% swelling value. Surface morphology shows an uneven and hollowsurface.